Halakhak: Defining the “National” in the Humor of Philippine Popular Culture - Ancheta, Maria Rhodora G. (Thammasat Review, 2015)
The main aim of this paper is to examine specific and strategic popular cultural texts in order to revaluate Philippine comedy and humor. The paper explores how its deployment of comic strategies illuminate and underscore the creation of communitas in Filipino terms, by re-presenting the quirks, traditions, eccentricities of Philippine society, not now as “ersatz,” inferior versions of Western comic forms, but as reconfigurations and reconstructions of a unique Filipino cultural psyche. I wish to note in this paper how humor becomes an operating textual and cultural device that reconstitute accepted beliefs, render moot and fracture hegemonic normalcies by using comic strategies to open possibilities for deploying the comic within the nation and the region as a way of understanding a Filipino/Asian identity.